The Implementation of Using Quick Response Codes in Listening Comprehension for Senior High School (RETAIN, 2020)
Listening is an active activity because their brain is working to catch the information and understand what the speaker is saying. However, teaching listening is not easy. To overcome this problem, mobile learning (m-learning) as a tool of mobile technology can be used for media of learning listening. QR Codes is one of the m-learning media that can be used for it. Meanwhile, the objective of this study are to describe the implementation of using QR Codes in listening comprehension and the student’s response during the implementation of using QR Codes as a media in listening. This study was applied to the tenth grades of Senir High School and cinducted in qualitative research design. The instruments used to collect the data are observation field note and the answer to the questionnaire given to them. Based on the data, the result of this study shows the implementation of using QR Codes in learning is appropriate to increase the students’ willingness to learn listening. Keywords: listening, learning media, mobile learning (m-learning), Quick Response Codes (QR codes) Medengarkan adalah sebuah aktivitas aktif karena otak mereka akan bekerja untuk menangkap informasi yang mereka dengarkan dan memahami apa yang pembicara katakan. Akan tetapi, mengajar mendengarkan itu tidak mudah. Untuk mengatasi masalah ini, pembelajaran seluler (m-learning)sebagai alat teknologi seluler bisa digunakan untuk media belajar mendengaran. QR Codes adalah salah satu media pembelajaran seluler yang bisa digunakan untuk belajar mendengarkan. Sementara itu, tujuan dari penelitian ini adalah untuk mendeskripsikan penerapan penggunaan QR Codes dalam pemahaman mendengarkan dan respon siswa selama penerapan penggunaan QR Codes sebagai media untuk mendengarkan. Penelitian ini diterapkan di kelas X SMA dengan desain penelitian kualitatif. Peneliti melakukan pengamatan dan memberikan kuisioner kepada siswa. Instrumen yang digunakan untuk mengumpulkan data adalah catatan observasi dan jawaban kuisioner yang diberikan kepada siswa. Berdasarkan data yang diperoleh, hasil dari penelitian ini menunjukkan penerapan penggunaan QR Codes dalam pembelajaran mendengarkan sesuai untuk meningkatkan minat belajar mendengarkan siswa.Kata Kunci: mendengarkan, media belajar, pembelajaran seluler (m-learning), Quick Response Codes